Successful Treatment of a Bilateral Lower Palpebral MALT Lymphoma with Rapid Arc: Description of a New Technique - Issam Lalya; Laila Baddouh; Keltoum Dahmani; Noha Zaghba; Khalid Andaloussi; Mohamed Elmarjany; Khalid Hadadi; Hassan Sifat; Hamid Mansouri (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2016)
Primary  MALT  lymphoma  of  the  eyelids  is  a  rare  disease;chronic infection by Chlamydophila psittaci has been identified as a possible causative agent, but other pathogens may be implicated such Hepatitis C virus and Helicobacter Pylori. This tumor is considered to have an indolent natural history and a favorable prognosis. Radiation therapy with moderate doses is the corner stone of treatment offering excellent local control with low complications rate. We report herein the radiation therapy treatment plan of a 65-year-old man presented to  our  department  with  a  primary  bilateral  lower  palpebral  MALT lymphoma.  CT  scan  of  2.5-mm  slice  thickness  in  supine  position was  realized.  A  bolus  of  1cm  adapted  to  closed  eyes  (glasses-like) were  placed  and  fixed  to  palpebral  surface  (Figures  1,2),  before immobilization  with  standard  thermoplastic  mask  (Figure  3).  The clinical target volume included the tumor, lachrymal glands and the entire orbit. The planning target volume was obtained by automatic margin  of  5  mm  around  the  clinical  target  volume.  Optic  nerves,eyeballs  and  lens  were ontoured  as  organs  at  risk.